Direct‐acting antiviral drug approvals for treatment of chronic hepatitis C virus infection: Scientific and regulatory approaches to clinical trial designs - Mishra, Poonam; Murray, Jeffrey; Birnkrant, Debra (Hepatology (Baltimore, Md.), 2015)
Therapeutic options for treatment of chronic hepatitis C have improved substantially since the approval of direct‐acting antiviral agents (DAAs). Several interferon (IFN)‐free or IFN‐ and ribavirin (RBV)‐free treatment regimens with shorter durations and improved efficacy and safety profiles are now available. The U.S. Food and Drug Administration (FDA) used several scientific approaches and regulatory mechanisms, such as (1) use of a “validated” surrogate (sustained virological response) for a primary endpoint, (2) shortening the time point for measuring the surrogate by 12 weeks, (3) use of historical controls when clinically appropriate, and (4) use of modeling when scientifically sound to extend treatment indications to subpopulations not fully evaluated in clinical trials, which had an impact on DAA development and subsequent approvals. This article intends to provide increased transparency about the FDA's scientific approaches and regulatory processes that supported drug development and marketing approval of DAAs for treatment of hepatitis C, a serious, life‐threatening infection. (Hepatology 2015;62:1298‐1303)